Global research trends of immunosenescence and immunotherapy: A bibliometric study - Wendi Li; Lin Xiao; Haiyang Li; Wei Cui (Human Vaccines & Immunotherapeutics)
Immunosenescence refers to the gradual decline in immune system function with age, increasing susceptibility to infections and cancer in the elderly. The advent of novel immunotherapies has revolutionized the field of cancer treatment. However, the majority of patients exhibit poor re-sponses to immunotherapy, with immunosenescence likely playing a significant role. In recent years, significant progress has been made in understanding the interplay between immunosenescence and immunotherapy. Our research aims to explore the prospects and development trends in the field of immunosenescence and immunotherapy using a bibliometric analysis. Relevant articles were collected from the Web of Science Core Collection (WoSCC) (retrieved on July 20, 2024). Primary bibliometric characteristics were analyzed using the R package “Biblio-metrix,” and keyword co-occurrence analysis and visualization were conducted using VOSviewer. A total of 213 English-language original research and review articles spanning 35 years were re-trieved for bibliometric analysis. There was a surge in publications in this field starting in 2017. The United States and China contributed the most articles. Frontiers in Immunology was the most productive journal, while the University of California System was the highest contributing institution. Besse Benjamin from France emerged as the most influential researcher in this field. Popular keywords included “nivolumab,” “T cells,” “dendritic cells,” and “regulatory T cells.” The “immunosenescence-associated secretory phenotype” has become a new hotspot, with immune checkpoint inhibitors remaining a central theme in this domain. The field of immunosenescence and immunotherapy is entering a phase of rapid development and will continue to hold significant value in future research.